Isolation and Identification of Aspergillus sp. in Tilapia (Oreochromis sp.) Sold for Consumption in Bogor - Arumugam, Khirthanaa; Budiono, Novericko Ginger; Widyananta, Budhy Jasa (Universitas Airlangga, 2024)
This study investigated the prevalence of Aspergillus sp. in tilapia sold for consumption at Pasarean Village in Bogor District. A total of 50 fish were sampled for further investigation. The clinical signs of fish were eroded fins, gills, haemorrhages, and wounds. The presence of pathogenic fungi was confirmed through fungal isolation from the skin, gills, and cloaca and subsequent culturing on potato dextrose agar. Macroscopic and microscopic observations determined Aspergillus sp. The results showed that four Aspergillus species were identified i.e., A. terreus (2%), A. flavus (4%), A. fumigatus (42%), and A. niger (4%), with the occurrence of co-infection between A. fumigatus and A. flavus (2%); A. fumigatus and A. terreus (2%); and between A. fumigatus, A. flavus, and A. niger (2%) reported a total prevalence of 58%. Further study is necessary to mitigate the crucial impact of fungal diseases in aquaculture systems, leading to effective prevention and control strategies, thus ensuring the safety and sustainability of aquaculture practices in Indonesia.